A Analysis of the Influence of the AIDA Method ( Attention, Interest, Desire, Action) on Purchasing Decisions for Halal-Labeled Fast Food for FAI UMSU Students - Gea, Ulfa Mardiah; Rahmayati (Journal of Islamic Economics Perspectives, 2024)
This study is to determine how consumer purchasing decisions for halal-labeled fast food products are influenced by the AIDA (attention, interest, desire, action) method applied. As a marketing strategy, the AIDA approach is used to determine how much attention, interest, desire, and consumer behavior can influence the decision to buy fast food that has received halal certification. This study uses a quantitative approach by distributing questionnaires to 100 respondents from 925 FAI UMSU students. The sample collected in this study was purposive sampling, meaning that the sample was based on certain criteria, namely FAI UMSU students from 2020 - 2023. The results showed that simultaneously the attention, interest, desire, and action variables influenced the decision to purchase halal-labeled fast food. Based on the coefficient of determination, the AIDA approach influences 73.1% of purchasing decisions for halal-labeled fast food. The remaining 26.9% is influenced by factors not included in the research model. Keywords: AIDA, Purchase Decision, halal label Keywords: AIDA, Purchase Decision, halal label